PERILAKU MASYARAKAT DALAM MENGOLAH SAMPAH DI DESA SUNGAI GOLANG, KECAMATANC KELAYANG, KABUPATEN INDRAGIRI HULU - Nur Rahma Sundari; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The waste problem is a fact faced by the community in Sungai Golang Village, the presence of waste can cause environmental pollution and is dangerous for public health if not managed properly. This study aims to determine: 1.) community behavior in managing waste (covering waste processing methods, public knowledge of waste) 2.) factors that influence people in managing waste (including educational factors, economic factors, and cultural factors). The method used in this research is descriptive quantitative analysis approach. The results obtained are 1.) community behavior in the process of managing waste there are various ways ranging from separating wet and dry waste, then burning it and the community also knows how to manage waste properly and correctly, community behavior in processing waste in protecting the environment so that it stay clean and healthy is classified as a positive category 2.) the factors that influence the community in managing waste are self-awareness of environmental cleanliness and the means to support the process of processing waste which are also not available are factors that influence the community in processing waste, then the education factor about how widely public knowledge about waste and good processing methods, economic and income factors as well as cultural factors about community habits that affect how to process waste. Keywords: Behavior, Society, Waste Management.